Fabricated the new world of 3D printing - Lipson, Hod; Kurman, Melba (John Wiley & Sons, Inc, 2013)
This book tells the story of 3D printers, humble manufacturing machines that are bursting out of the factory and into schools, kitchens, hospitals, even onto the fashion catwalk. The book describes the emerging world of printable products, where people design and 3D print their own creations as easily as they edit an online document. A 3D printer transforms digital information into a physical object by carrying out instructions from an electronic design file, or "blueprint